Distribution of SPARC during neovascularisation of degenerative aortic stenosis. Issue 12 (18th May 2006) - Charest, A; Pépin, A; Shetty, R; Côté, C; Voisine, P; Dagenais, F; Pibarot, P; Mathieu, P
Abstract : Objective: To examine the hypothesis that degenerative aortic stenosis (AS) is associated with the development of blood vessels and the expression of the secreted protein, acidic and rich in cysteine/osteonectin (SPARC), a matricellular protein that is involved in ossification, the modulation of angiogenesis and the production of metalloproteinases. Methods: 30 surgically excised AS valves and 20 normal aortic valves were studied. Results: Blood vessels were detected in the aortic valves from patients with degenerative AS, whereas normal valves were avascular structures. Blood vessels in AS valves expressed endothelial nitric oxide synthase, CD34 and von Willebrand factor (vWF). Blood vessels were located in three distinct regions: near calcified nodules, under the leaflet border and in rich cellular areas forming cell islands. Blood vessels were predominantly present in early and intermediate grades of calcification. Cell islands were densely populated by CD45-positive cells where endothelial cells (CD34+, vWF+) forming cord-like structures were present. Immunoblotting detected SPARC only in AS valves and immunohistological analysis located SPARC in mature blood vessels. The proportion of blood vessels positive for SPARC was higher in valves with a lower grade of calcification. In cell islands, SPARC was distributed to mature blood vessels and to macrophages, where it co-located with matrix metalloproteinase-9, whereas no expression was detected in endothelial cells forming cord-like structures. Conclusion: The localisation of SPARC to mature blood vessels and its predominant expression in AS valves with a lower calcification grade suggest that the spatial and temporal distribution of this matricellular protein is tightly controlled to participate in the neovascularisation of AS valves.